Pengaruh Economic Value Added (EVA) dan Market Value Added (MVA) Terhadap Rertun Saham pada Perusahaan Manufaktur Sub Sektor Otomotif Periode Tahun 2010-2018 - Deni Sunaryo (Universitas Islam Bandung, 2019)
This research aims to determine the influence of EVA on Return shares, MVA against Return shares. and EVA, MVA jointly (simultaneous) against Return shares. Samples of this research as many as 7 companies manufacturing automotive subsectors listed on IDX period 2010-2018 obtained by purposive sampling method. Data analysis techniques use descriptive statistical analysis, test prerequisite analysis, and multiple linear regression analyses. The results showed: EVA had no effect and was insignificant to Return shares, the MVA had no effect and insignificant to Return shares and EVA, MVA, jointly (simultaneous) gave a positive and significant influence on Return stock.